MELACAK AKAR KEKERASAN ANTAR AGAMA SEBAGAI DASAR KONFLIK SOSIAL - muchalis muchalis (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2016)
This article will explain about the violence and conflict as the basis of religious learning. It is based on the two main motives: Islam as a universal religion that offers peace and Islam as a solution for the welfare of the poor and a comprehensive religion containing a lot of universal values. Therefore, Islam is not merely religion that discuss issues of economic and political interests, but further it is probably a fundamental foundation in the search for solutions on the basis of violence and social conflicts occur in community. Hence, this paper further describes how Islam as a religion of self-defense may become a way to God (vertical) as the basis for the social problems occur either individually, in groups or both.